A Rare Case of a Cervical Thymic Cyst Presenting in Adulthood - Smith, Blaine D.; Schild, Michael H.; Jiang, Xiaoyin “Sara”; Kahmke, Russel R. (Case Reports in Otolaryngology, 2020)
The cervical thymic cyst (CTC) is a rare, benign neck mass that most commonly presents in the pediatric population. These entities can occur anywhere along the normal path of descent of the thymus from the mandible to the sternal notch, and extension into the mediastinum has been observed. The presentation of these masses is often characterized by a painless, enlarging neck mass in a child during the first decade of life. Although most patients are asymptomatic, abutment of the cyst against local structures has led to a variety of presentations including respiratory distress. These rare lesions are noted to have a male predominance and most commonly present on the left side of the neck. We present the rare case of a 19-year-old male who presented with a left-sided painless, cystic neck mass. He underwent a computed tomography scan of the neck which showed a large cystic mass in the left neck deep to the sternocleidomastoid muscle. Preoperatively, the diagnosis of an infected third branchial cyst was favored. The lesion was completely excised in the operating room. Final pathology was consistent with a CTC. The CTC is an uncommon benign process that often presents as an asymptomatic cystic neck mass. Knowledge of the clinical presentation, diagnostic process, and treatment of these rare lesions is essential for the Otolaryngologist.